2019
DOI: 10.1542/peds.2019-1183
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality Disparities Between Transgender and Cisgender Adolescents

Abstract: BACKGROUND AND OBJECTIVES: Emerging evidence indicates transgender adolescents (TGAs) exhibit elevated rates of suicidal ideation and attempt compared with cisgender adolescents (CGAs). Less is known about risk among subgroups of TGAs because of limited measures of gender identity in previous studies. We examined disparities in suicidality across the full spectrum of suicidality between TGAs and CGAs and examined risk for suicidality within TGA subgroups. METHODS: Adolescents aged 14 to 18 completed a cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 36 publications
(64 reference statements)
4
93
2
3
Order By: Relevance
“…The current study had focused on population of Arab ethnic minority in Israel. Cross-cultural comparison has revealed a wide variety of suicidal ideation (Page et al,2013), and being affiliated with minority groups, such as racial (Lindsey et al, 2019) or sexual identity (Thoma et al, 2019) minorities, has been found associated with higher risk of NSSI and suicidality. However, studies within the Arab population in Israel revealed high communal and traditional attitudes (Al-Krenawi, 2010;Sharabi, 2014), which had been established as substantial protective factors (Foster et al, 2017;Kuentzel et al, 2012;Martin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The current study had focused on population of Arab ethnic minority in Israel. Cross-cultural comparison has revealed a wide variety of suicidal ideation (Page et al,2013), and being affiliated with minority groups, such as racial (Lindsey et al, 2019) or sexual identity (Thoma et al, 2019) minorities, has been found associated with higher risk of NSSI and suicidality. However, studies within the Arab population in Israel revealed high communal and traditional attitudes (Al-Krenawi, 2010;Sharabi, 2014), which had been established as substantial protective factors (Foster et al, 2017;Kuentzel et al, 2012;Martin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 9 There are also a number of studies reporting a high percentage of suicidal ideation, self-harm, and suicide attempts in adolescents with gender dysphoria. 10 , 11 , 12 , 13 Compared with their cisgender peers, TGNC youth are more likely to report mental health problems such as anxiety, depression, and suicidal ideation. 1 , 14 Moreover, within the school environment, transgender adolescents are vulnerable to harassment and bullying.…”
Section: Introductionmentioning
confidence: 99%
“…Durante a fase da adolescência, qualquer comportamento negativo com relação à identidade de gênero de adolescentes transgêneros, pode acarretar em prejuízo para a saúde destes (Yadegarfard et al, 2014). Ideação e tentativa de suicídio são mais frequentes em adolescentes transgêneros do que cisgêneros (Thoma et al, 2019). O desejo sexual, para parte dos nossos entrevistados, surge nas pessoas de acordo com sua natureza, independente das influências que sofram.…”
Section: Discussionunclassified